Combining Postmortem Cerebrospinal Fluid Biochemistry With Lung-to-Body Ratio to Aid the Diagnosis of Salt Water Drowning. (December 2020) - Garland, Jack; Ondruschka, Benjamin; Palmiere, Cristian; Hu, Mindy; Philcox, Winston; Hensby-Bennett, Sarah; Stables, Simon; Kesha, Kilak; Glenn, Charley; Morrow, Paul; Tse, Rexson
Abstract : Abstract: Diagnosing drowning as a cause of death can pose many challenges for the forensic pathologist and a number of ancillary tests have been proposed to assist in the diagnosis, whether the body was in salt water or fresh water. Although elevated vitreous humor sodium and chloride is a reliable marker, its limitation to prolonged immersion has resulted in the recent investigation of cerebrospinal fluid (CSF) sodium and chloride as alternative matrix in cases of longer or unknown immersion times. This study investigated postmortem CSF from lumbar puncture (CSF_L_Na_Cl) and ventricular aspiration (CSF_Vent_Na_Cl), as well as lung/body (LB) ratio in the diagnosis of salt water drowning and performed comparison and combination testing of methods to improve diagnostic accuracy of the drowning diagnosis. This study found that CSF_L_Na_Cl was the most accurate method (89%) in the given cohort, but that CSF_Vent_Na_Cl and LB combined was the second most accurate method (83%), exceeding CSF_Vent_Na_Cl (77%) and LB (81%) used alone. These findings are useful for stratifying and prioritizing postmortem samples in the investigation of salt water drowning and also have significance for future studies using this methodology to combine and compare the accuracy of different investigations.